Mufti's Views And Fatwa Authorities On Ihdad: Implementation Challenges Among Working Women - Norita Kamaruddin; Zanariah Dimon; Syh.Noorul Madihah Syed Husin; Norazla Abdul Wahab; Ramazan Korkut (Universiti Sains Islam Malaysia, 2026)
Ihdad is a religious obligation imposed on Muslim women whose husbands have passed away, requiring a mourning period of four months and ten days that includes prohibitions against adornment, the use of fragrance, and the requirement to remain in the marital home. However, the enforcement of fatwas on ihdad presents significant challenges for working women who face the demands of employment, family responsibilities, and the realities of modern life. This study aims to examine ihdad-related fatwas in Malaysia in terms of their legal provisions, the lived experiences of working women, and the need to develop a more practical support model. A qualitative design was employed, combining document analysis, focus group discussions (FGD), and semi-structured interviews with widows undergoing ihdad as well as representatives of employers. The data were thematically analyzed using atlas.ti. The findings reveal a gap between fatwa prescriptions and the realities of working women, particularly regarding the necessity of leaving the home for work, fulfilling professional commitments, and sustaining household finances. The study proposes the development of an Ihdad Support Model encompassing policy, financial, emotional, social, and educational dimensions, ensuring that religious obligations are upheld without neglecting the contemporary needs of working women. This article contributes to strengthening fatwa-related policymaking and employment regulations, offering a more inclusive and holistic framework to support widows in the aftermath of their husbands’ death.